Effectiveness of Magnetic Nanocomposites Modified with Reduced Graphene Oxide Derived from Spent Coffee Grounds for Pharmaceutical Waste Remediation - Khairani, Raisya Fakhira; Nurqisthi, Faisha; Nuari, Sindhi Ika; Herwinta, Syifa Rahmalia; Rahma, Aqilla Irfa Muthia; Eddy, Diana Rakhmawaty (Departemen Kimia, 2025)
The Covid-19 pandemic significantly inflluenced the growth of the pharmaceutical industry in Indonesia, leading to environmental challenges, particularly with the discharge of pharmaceutical wastewater. Traditional treatment methods, such as flocculation and coagulation, hav limitations as they produce large volumes of activated sludge. An alternative approach for remediating this wastewater is the use of magnetite nanocomposites modified with reduced graphene oxide. This material leverages the unique properties of reduced graphene oxide, enhancing the separation and transfer of electron-hole pairs generated in the photogeneration process and significantly reducing charge carrier recombination in the photocatalytic system. This study aims to determine the degradation precentage of pharmaceutical wastewater using magnetic nanocomposite materials synthesized via in-situ chemical co-precipitation. The degradation percentage achieved through photocatalytic testing was 38.34% in basic conditions, with a band gap value of 2.03 Ev, operating under visible light. The characterization techniques used in this research include XRD, TM-EDS, FTIR, and UV-vis-DRS.